IMPLEMENTATION OF REGISTRATION OF INDIVIDUAL COMPANIES THROUGH THE GENERAL LEGAL ADMINISTRATION SYSTEM ONLINE IN PEKANBARU CITY - Wahyuni Rizki; Irawan Harahap; Miftahul Haq (JILPR Journal Indonesia Law and Policy Review, 2026)
This study aims to analyze the implementation of Sole Proprietorship registration through the Online General Legal Administration System (AHU) in Pekanbaru City, identify obstacles encountered in its implementation, and examine efforts made to overcome these obstacles. Sole Proprietorship is a form of legal entity intended for Micro and Small Enterprises (MSEs) as regulated in Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law and Government Regulation Number 8 of 2021. This study uses a sociological legal research type with an empirical approach. Data were obtained through interviews with officials from the Riau Province Ministry of Law Regional Office, the Pekanbaru City Investment and One-Stop Integrated Service Office, and Micro and Small Enterprises, supported by literature studies. Data analysis was conducted qualitatively using descriptive methods. The results of the study indicate that the implementation of Sole Proprietorship registration through AHU Online in Pekanbaru City has been running in accordance with the provisions of laws and regulations and provides convenience in the form of a fast, simple, affordable process, and can be done electronically. However, its implementation has not been optimal due to various obstacles, including low understanding of MSEs regarding Sole Proprietorships (Private Partnerships), limited ability to use information technology, and suboptimal socialization and mentoring activities. Efforts made to overcome these obstacles include increasing socialization to the community, providing technical assistance to MSEs in the registration process through AHU Online, and strengthening coordination between relevant agencies to improve the effectiveness of policy implementation. Thus, continuous synergy is needed between the government and business actors so that the goal of establishing a Sole Proprietorship as a legal business instrument for MSEs can be optimally realized.